Isolation of microorganisms from landfill soil and the production of enzyme - Nur Suhaila, Anang Japar (2017)
Population growth with increasing consumption levels leads to abundant waste in Malaysia. In 2012, the average waste generation rate of Malaysia is 33,000 tons of waste per day with composition distribution of 46% food waste, 15% plastic, and 14% paper. Landfilling is the main solid waste management in Malaysia. However, the capacity of the existing landfill is decreasing as the waste generated is rapidly increasing. Waste disposed in landfill contains many types of bacteria with the potential to degrade the waste compound. The objectives of the study are to isolate and characterize the microorganisms from landfill soil and to produce the cellulase enzyme for waste degradation by culturing the isolated microbe. These enzymes are believed to have ability to accelerate the degradation of municipal solid waste in the biodegradation process. Soil samples for bacterial isolation were taken from Sungai Ikan Landfill in Terengganu. Characterization of bacteria was conducted via gram staining and morphology studies. In this study, screening tests with selective media demonstrated the ability of bacteria to produce cellulase. Bacteria with high ICMC index from screening test were taken as potential bacteria to give high production of cellulase. The production of cellulase was conducted and observed through cellulase production profile, which was determined based on the measurement of total cell dry weight and cellulase production after every 12 hours. Microorganisms found in landfill soil were 51 different species of microorganisms which are 39 Gram positive and 12 Gram negative. Among these 51 species, 34 species were cellulolytic microorganisms and able to produce cellulase enzymes. 3 different isolates with high ICMC index were analyzed for its enzymatic activity. Overall, the best microorganism was bacterial isolate D1 with optimum growth time of 24 h and highest cellulase activity (10.0716 U/mL).